Government size and output volatility: Should we forsake automatic stabilisation? - Xavier Debrun; Jean Pisani-Ferry; André Sapir (Bruegel, 2008)
[Introduction ...] The aim of this paper is to discuss this issue in the light of recent experience. It is divided into five sections. In section 2, we briefly discuss the economic benefits of macroeconomic stability and the rationale for government policies playing an active role in delivering it. Section 3 reviews the economic literature on the determinants of output volatility and its link with government size. Two separate strands of the literature are surveyed: cross-country studies focusing on OECD members and time-series studies of a single country, typically the United States. The cross-section studies confirm that countries with large governments tend to enjoy less output volatility, but also that there may be a threshold level beyond which the negative relationship disappears or even reverses. The studies that focus on the United States show, however, that the country has recently experienced an important reduction in output volatility, despite probably lying below this threshold and having witnessed a less pronounced increase in government size than most OECD countries. This suggests that something other than automatic stabilisation has been at work: an exogenous fall in volatility, an increase in market-based stabilisation, or an improvement in monetary policy. Section 4 shows descriptive evidence on the size of government, macroeconomic volatility and the role of fiscal stabilisation policies in supporting consumption smoothing in the OECD countries, including 11 euro area members. The evidence confirms the contrast between time-series and cross-sectional studies. The main finding, however, is that the negative correlation between government size and output volatility, which is a major finding of the literature, seems to vanish for more recent cross-country data. In the traditionally volatile, small government countries, volatility has decreased substantially while government size has grown less than elsewhere. Section 5 builds on these stylised facts to present new econometric estimates of the relationship between government size and output volatility using both time-series and cross-country information. We first confirm that the traditional link between government size and macroeconomic volatility disappeared during the 1990s. We then explore possible reasons for this breakdown, focusing on the role of improvements in the quality of monetary policy and on progress in financial development. The evidence suggests that monetary policy and financial development can both be substitutes for government size as a stabilising force, and that once this substitutability is taken into account, the relationship between government size and macroeconomic stability remains strong, though non-linear: the marginal effect of an increase in government size on output volatility is found to be negligible for public expenditure levels above 40 percent of GDP. Conclusions and policy implications are given in Section 6.
Keywords: 330; Finanzpolitik; Automatischer Stabilisator; Antizyklische Finanzpolitik; Sozialprodukt; Gesamtwirtschaftliche Produktion; Volatilität; EU-Staaten; USA